2018
DOI: 10.1007/s12035-018-1030-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by cognitive impairment and synaptic dysfunction. Adenosine is an important homeostatic modulator that controls the bioenergetic network in the brain through regulating receptor-evoked signaling pathways, bioenergetic machineries, and epigenetic-mediated gene regulation. Equilibrative nucleoside transporter 1 (ENT1) is a major adenosine transporter that recycles adenosine from the extracellular space. In the present study, we report that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 88 publications
4
53
1
Order By: Relevance
“…Several studies have shown that the levels of A 2A R expression change in AD is up to five times higher than those of normal levels (Orr et al, ). Also, in vivo data from traumatic brain injury or amyloid‐based models have demonstrated a similar range of A 2A R upsurge ranging from 1.5 to 12 fold (Zhao et al, ; Orr et al, ; Faivre et al, ; Lee et al, ). One could therefore argue that the A 2A R overexpression reached in our study is beyond the changes found in pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several studies have shown that the levels of A 2A R expression change in AD is up to five times higher than those of normal levels (Orr et al, ). Also, in vivo data from traumatic brain injury or amyloid‐based models have demonstrated a similar range of A 2A R upsurge ranging from 1.5 to 12 fold (Zhao et al, ; Orr et al, ; Faivre et al, ; Lee et al, ). One could therefore argue that the A 2A R overexpression reached in our study is beyond the changes found in pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 94%
“…A 2A R is a modulator of several physiological responses essential to brain homeostasis such as blood brain barrier maintenance, neurotransmitter release, and inflammation (Gołembiowska et al, ; Ouyang et al, ; Bhamidipati et al, ; Kim & Bynoe, ), processes that are highly associated with neurodegenerative diseases, such as AD and PD (Cunha, ). The relationship between A 2A R and AD in the control of cognitive impairment has been extensively observed in several experimental models (Canas et al, ; Laurent et al, 2014; Laurent et al, 2014; Lee et al, ; Silva et al, ). Upregulation of A 2A R in neurons was shown to induce aberrant phenotypic alterations during aging and in the early stages of AD (Temido‐Ferreira et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…170 Adenosine augmentation has been found beneficial in multiple neurological disorders, including AD. 171,172 However, further comprehension of the mechanism and the putative effects on adenosine receptors and downstream signaling pathways are crucial at this stage.…”
Section: The Modulation Of Aged Synapse By Adenosine a 2a Receptorsmentioning
confidence: 99%
“…Recent studies suggest that inactivated autophagy-related proteins in damaged neurons [14] represent a suitable target for experimental NDD therapy [15]. Although there is extensive literature on the accumulation of toxic proteins inside neuronal cells as a result of autophagy repression and its pharmacological correction [16], relatively few studies have addressed the possibility of targeting neuronal cells with aberrant signaling [17][18][19][20][21] by using alternate approaches, such as gene therapy. Below, we summarized the benefits of gene therapy application for NDD treatment.…”
Section: Introductionmentioning
confidence: 99%